Role of Regions in the Foreign Trade Activity of Russia in the Context of New Geopolitical Challenges - Linetsky, Aleksandr Fedorovich; Tarasov, Anatoly Grigoryevich; Kovalev, Viktor Evgenyevich (Economy of Regions, 2017)
The authors have considered both the role of territorial subjects of the Federation in the foreign trade activity of Russia and the characteristics of conditions for the implementation of foreign economic relations by the Russian regions. The hypothesis of the research suggests that in the current conditions of Russia’s participation in the World Trade Organization (WTO) and new geopolitical challenges in the foreign trade activity, the territorial subjects of the Federation more and more actively realize their constitutional right on international economic relatiens. The role of Russian regions in the development of the foreign trade activity of Russia constantly rises as a single center in modern conditions, is not able to manage all matters relating to foreign trade activity arising in the concrete region of the state. The relevance of the article consists in the need to investigate the change of conditions for the implementation of foreign economic activity by territorial subjects of the Federation as during the current period, regions play more important role in the development of the foreign trade activity of Russia. The authors assessed the impact of WTO, whose member Russia became in 2012 on its foreign trade. The assessment has shown an absence of any real notable positive or negative consequences. The politicization of world economy is the characteristic of the present stage of its development. Thus, the world markets are more dependent on political factors than on other ones. The results of the conducted research can be applied and used for the development and realization of the regional model and strategy of foreign trade activity. The future research will be focused on the development and improvement of the model of the implementation of foreign economic activity by the territorial subjects of the Russian Federation.